Improvement of N, P, and K availability of post-brick mining soil to increase maize yield by applying different types of biochar - Widowati, Widowati; Wilujeng, Retno; Nurhidayati, Nurhidayati; Indrayatie, Eko Rini (Journal of Degraded and Mining Lands Management, 2024)
The low fertility of post-brick mining soil may be improved by applying biochar to the soil because biochar is an excellent soil amendment, although its quality varies depending on the raw materials used. Therefore, soil fertility, nutrient availability, and crop yields are affected by the type and amount of biochar added to soils. This study examined the effect of types and dosages of biochar on nitrogen, phosphorus, and potassium availability of post-brick mining soil to increase maize yield. The treatment combinations of biochar dosages (0 t ha-1, 15 t ha-1, 30 t ha-1, and 45 t ha-1) and biochar types (coconut shell, wood, and rice husk biochars) were arranged in randomized block design with three replications. Each treatment plot measuring 4 m x 4.5 m was planted with maize seeds with a planting space of 80 cm x 25 cm. Urea (135 kg N ha-1), SP36 (36 kg P2O5 ha-1), and KCl (110 kg K2O ha-1) were applied as basal fertilizers. The results showed that at eight weeks after biochar application, the amount and type of biochar positively affected maize yield. The application of rice-husk biochar at 30 t ha-1 resulted in the highest maize yield. The application of each type of biochar at 45 t ha-1 yielded the highest increase in the availability of nitrogen, phosphorus, and potassium in the soil.